2021
DOI: 10.3390/genes12121960
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination as a Fundamental Genome Surveillance Mechanism during DNA Replication

Abstract: Accurate and complete genome replication is a fundamental cellular process for the proper transfer of genetic material to cell progenies, normal cell growth, and genome stability. However, a plethora of extrinsic and intrinsic factors challenge individual DNA replication forks and cause replication stress (RS), a hallmark of cancer. When challenged by RS, cells deploy an extensive range of mechanisms to safeguard replicating genomes and limit the burden of DNA damage. Prominent among those is homologous recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Based on the pictures obtained, we can conclude that the main TR rearrangement is going on in the periCEN region not involving the extra sequences from the chromosome arms as the library hypothesis supposes [26,54]. The features of the DNA replication under replication stress [57], which is inevitable during speciation, are sufficient to cause the amplification of the TR monomer, which varied just in the periCEN region.…”
Section: Library Hypothesismentioning
confidence: 79%
“…Based on the pictures obtained, we can conclude that the main TR rearrangement is going on in the periCEN region not involving the extra sequences from the chromosome arms as the library hypothesis supposes [26,54]. The features of the DNA replication under replication stress [57], which is inevitable during speciation, are sufficient to cause the amplification of the TR monomer, which varied just in the periCEN region.…”
Section: Library Hypothesismentioning
confidence: 79%
“…Previously, we showed that the recombination mediator Rad52 is part of the megafocus ( Sabatinos et al 2015 ) and, consistent with this, we also saw recruitment of Rad51 and Rad54. This was not a surprise, since numerous studies suggest that HR proteins, particularly Rad51, play a key role in replication fork stress response ( Bhat and Cortez 2018 ; Nickoloff et al 2021 ; Spies et al 2021 ). However, the GCR and chromosome loss associated with mcm4-dg is not significantly affected by the loss of HR proteins ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have shown that CX-5461 treatment in macrophages is indeed associated with a transcriptome signature related to DNA repair. Specifically, CX-5461 downregulates the expression of multiple genes involved in homologous recombination, an important pathway responsible for repairing double-strand breaks and maintaining genome stability ( Spies et al, 2021 ). These data seem to be paradoxical to the observed activation of DDR in CX-5461-treated cells, and the physiological significance of CX-5461-induced downregulations of the DDR genes remain elusive.…”
Section: Discussionmentioning
confidence: 99%